2022
DOI: 10.1038/s41467-022-30311-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic lethality between TP53 and ENDOD1

Abstract: The atypical nuclease ENDOD1 functions with cGAS-STING in innate immunity. Here we identify a previously uncharacterized ENDOD1 function in DNA repair. ENDOD1 is enriched in the nucleus following H2O2 treatment and ENDOD1−/− cells show increased PARP chromatin-association. Loss of ENDOD1 function is synthetic lethal with homologous recombination defects, with affected cells accumulating DNA double strand breaks. Remarkably, we also uncover an additional synthetic lethality between ENDOD1 and p53. ENDOD1 deplet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Of these, TP53 and TTN were detected with higher rates than other genes. Indeed, TP53 mutations were associated with multiple cancers as a potential therapeutic target [33–35], and synthetic lethality between TP53 and ENDOD1 implicated ENDOD1 as a potential cancer‐specific target for drug discovery [36]. Many of these 45 genes were involved in multiple interactions with other genes (median value = 72) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, TP53 and TTN were detected with higher rates than other genes. Indeed, TP53 mutations were associated with multiple cancers as a potential therapeutic target [33–35], and synthetic lethality between TP53 and ENDOD1 implicated ENDOD1 as a potential cancer‐specific target for drug discovery [36]. Many of these 45 genes were involved in multiple interactions with other genes (median value = 72) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This underlines the potential for SL treatment using PARPi. In previous work we identified the atypical nuclease ENDOD1 as a protein required in human cells to reduce the levels of trapped PARP and showed that ENDOD1 ablated cells were synthetic lethal with homologous recombination defects 26 . Here we show knockdown of ENDOD1 causes increased levels of DNA damage and forces cytotoxicity in the context of HBx expression and, using xenografts, show that knockdown of ENDOD1 by whole animal siRNA results in reduced tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…We recently uncovered an atypical endonuclease (ENDOD1) that counteracts PARP trapping on damaged chromatin 26 and demonstrated cell lethality upon concomitant ENDOD1-HR ablation. This potentially establishes a second therapeutic SL pair other than PARPi-HRD.…”
Section: Targeting Hbv-induced Hrd Suppresses the Disease Progression...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, siRNA against human ENDOD1 significantly inhibited the growth of TP53‐mutated xenograft tumors in EndoD1‐systemic knockdown mice. Therefore, ENDOD1 is an attractive synthetic lethal target for TP53 mutated cancers, which accounts for approximately 50% of cancers 72 . CHK1 is a crucial replication stress checkpoint kinase that maintains genome stability by controlling the cell cycle in response to DNA damage 73,74 .…”
Section: Functional Connection Of Sl In Individual Cancer Cellsmentioning
confidence: 99%